Overview awareness and satisfaction Universitas Jambi medical students towards the use of social media as an oral health literacy platform - Wijayanti, Zilzikridini; Hardiningsih, Denok Tri; Perkasa, Tengku Arief Buana; Amatullah, Afifah (Proceedings Academic Universitas Jambi, 2025)
Background: Social media has changed how people view oral health literacy, thus potentially increasing user awareness and satisfaction with oral health knowledge, especially among medical students. Objective: Specifically observing the awareness and satisfaction of medical students at University of Jambi toward using social media as an oral health literacy platform Methods: This observational cross-sectional study uses a non-probability purposive sampling design with the criteriia of medical students at University of Jambi who are still active and use social media to seek oral helath literacy. This study uses a special questionnaire about what platfoms are frequenly used and what sources of information ore commonly viewed to increase respondent literacy and a Likert scale to observe satisfaction. SPSS is used to find the frequency distribution. Results: The 292 respondents, the most widely used platform by medical students at University of Jambi is Instagram (10,3%) in the 19-59 age group (25,9%), in the class of 2025 (22%), and among female gender (22%). The most frequently viewed source of information by respondents is the account of a dentist/dental specialist (8,3%) in the 19-59 age group, the class of 2022 (27,7%), and most dominantly in female students (23,3%). The satisfaction level of the majority of respondents was “Satisfied” (53,3%), which wa mostly felt by the 19-59 age group, women, and the class of 2023. Conclusion: The frequency distribution of awareness and satisfaction that studied respondents, specifically medical students, hand unique and diverse frequency distribution in using social media as an oral health literacy platform.